Analisis Kebijakan Program Sekolah Penggerak di SD Pangudi Utami Temanggung - Astuti, Anastasia Nana; Egar, Ngasbun; Abdullah, Ghufron (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The Sekolah Penggerak program is an effort to promote educational unit transformation toward a holistic improvement of the study result among students, which covers the literation, numeration, and character aspects. The transformation begins with building high-quality human resources, i.e., the Principal and Teachers. This study is aimed at further analyzing the implementation of the Sekolah Penggerak policy, which is a part of the Independent Learning (Merdeka Belajar) policy, in Pangudi Utami elementary school. The Public Policy Implementation theory by Edward III is used, which consists of four aspects, i.e., communication, resources, disposition, and bureaucratic structure that takes part in the policy implementation. The study uses the descriptive-qualitative approach, which enables addressing the problem statement as made by the researcher. Data are collected through observation, interviews, and documentation. As to the data analysis method, the researcher went through the data collection, data processing, data presentation, and conclusion drawing stages. The result of the study indicates that the implementation of the Sekolah Penggerak program in Pangudi Utami elementary school in Temanggung has covered the communication aspect, both with the teachers, educational staff, and the relevant Education Office, the BBPMP, and the BBGP as the agency of the Ministry of Education, Culture, Research, and Technology of Indonesia. It also addresses the resources, disposition, and bureaucratic structure aspect despite the constraints during the first year of the implementation.